1992
DOI: 10.1021/bi00128a029
|View full text |Cite
|
Sign up to set email alerts
|

A simple spectral-driven procedure for the refinement of DNA structures by NMR spectroscopy

Abstract: We have developed a simple and quantitative procedure (SPEDREF) for the refinement of DNA structures using experimental two-dimensional nuclear Overhauser effect (2D NOE) data. The procedure calculates the simulated 2D NOE spectrum using the full matrix relaxation method on the basis of a molecular model. The volume of all NOE peaks is measured and compared between the experimental and the calculated spectra. The difference of the experimental and simulated volumes is minimized by a conjugated gradient procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 24 publications
1
76
0
Order By: Relevance
“…2A, there is no interruption of the connectivity for sequential assignment and every aromatic proton (H 6 and H s) has crosspeaks to the HZlH z' of its own sugar and the sugar on the 3' side, confirming the helical nature of the backbone. To have a more definitive view of the possible structure, several models (including blunt-ended 6-bp duplexes with type-I or type-II G-A mismatches, or a 5-bp duplex with a 3'-overhang G, all with an overall B or A conformation) were constructed and subjected to NOE-constrained refinement by the procedure SPEDREF [11] and a simulated annealing (SA) procedure using X-PLOR [12,15]. Our results indicated that the most plausibe model is a 6-bp B-DNA duplex with type-I G-A base pairs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A, there is no interruption of the connectivity for sequential assignment and every aromatic proton (H 6 and H s) has crosspeaks to the HZlH z' of its own sugar and the sugar on the 3' side, confirming the helical nature of the backbone. To have a more definitive view of the possible structure, several models (including blunt-ended 6-bp duplexes with type-I or type-II G-A mismatches, or a 5-bp duplex with a 3'-overhang G, all with an overall B or A conformation) were constructed and subjected to NOE-constrained refinement by the procedure SPEDREF [11] and a simulated annealing (SA) procedure using X-PLOR [12,15]. Our results indicated that the most plausibe model is a 6-bp B-DNA duplex with type-I G-A base pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The deblocked oligonucleotides were purified by Sepharose G-50 column chromatography. Solutions of the DNA oligomers (-5 mM duplex) with 150 mM NaCI and 50 mM 'phosphate buffer (pH 7.0) were prepared in 0.5 mi of I)20 as described earlier [11,12]. NMR spectra were collected on either a GE GN500 or a Varian VXR500 500 MHz spectrometer and the data were processed with FELIX via [13].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrals from the two-dimensional NOESY data set were measured as described by Robinson and Wang [26]. Refinement of the starting model was carried out by the sequence of procedures comprising the SPEDREF package [26].…”
Section: Methodsmentioning
confidence: 99%
“…For DNA hexamer duplex, the overall molecular tumbling is effectively isotropic and is well-approximated by a single correlation time t c (Robinson & Wang, 1992). Assuming simple and rigid molecular motion, t c is related to T 1 and T 2 by equation (1) (Suzuki et al, 1986):…”
Section: Noe-derived Distance Constraintsmentioning
confidence: 99%